Collaborative Governance in Off-site Anoa Conservation at The Anoa Breeding Center of The Manado Environment and Forestry Research and Development Institute - Bambang Subatin; Agus Pramusinto (Policy & Governance Review, 2019)
Collaborative governance has, currently, become an alternative to resolving public issues, wherein the government is suggested to collaborate with cross-sector organizations. Although several collaborative efforts developed by the government were reported to have failed, there are a number of successful collaborations established to resolve various issues. The main objective of this study is to analyze why did the collaboration process of the off-site anoa conservation through the Anoa Breeding Center (ABC) succeed in increasing the anoa population. This study employed the qualitative descriptive methodology. The data collection techniques used were literature study, observation, and interviews with stakeholders involved in ABC activities. The study results show that the collaboration in managing ABC was successful and it effectively resolved the problems confronted in the off-site anoa conservation due to active role of the administrators in realizing extensive participation, establishing and maintaining trust, as well as running a transparent process among the actors. The established collaboration is supported by a leadership that facilitated the implementation of the collaboration process. The collaboration is carried out formally as stipulated in the MoU made, as well as informally on the basis of the trust developed. The determining factors in the success of the collaboration in the off-site anoa conservation at ABC are the presence of process transparency, clear basic values, scope of actors involved, and facilitative leadership in the collaboration effort.